Adaptation pedagang kaki lima the Lockdown Policy in the Morning Market, Wonoayu District, Sidoarjo Regency - Aida Kurniawati; Muzayanah Muzayanah; Nugroho Hari Purnomo; Eko Budiyanto (USN Kolaka, 2021)
Covid 19 is a pandemic that does not know when it will end. This pandemic has had an impact on various sectors, especially the economy. The policy set by the government in the form of a lockdown has a negative impact on the community's economy, especially small traders. The purpose of this study was to determine the adaptation of street vendors to the lockdown policy. This research is qualitative research with the number of respondents being 105 street vendors. This study uses a sample of 15 people, with the reason that this trader has been selling for more than 1 year. The results of the study obtained a description of the characteristics of male street vendors amounting to 81%, the age of traders between 15-30 years is the highest number of ages reaching 62%, the most traders' education is a high school by 44%, traders from outside Wonoayu sub-district are 81 % and their average income is 69% below Rp. 100,000.00 per day. The adaptation of traders during the lockdown is to remain with the same type of merchandise by 81%, 19% of traders have changed the type of merchandise. Merchants switch places of sale is 75%. As much as 56% of merchandise transfers, their average sales model remains off at 69% while those who move to online are 31%. From the results of the research, the PKL's turnover decreased by 75%, while the turnover increased by 25%.